Is Helicobacter pylori Infection Associated with Celiac Disease? A Meta-analysis - Min Yue; Qiang Chen; Xinxin Zhou; Lan Li; Chao Lu (Turkish Journal of Gastroenterology, 2022)
Background: Some studies have reported the correlation between Helicobacter pylori and celiac disease (CD), but the results lack consistency. This meta-analysis aimed to quantify the relationship between H. pylori and CD. In addition, the study also analyzed the impact of H. pylori on the symptoms and classification of CD. Methods: Studies published up to September 1, 2020 on 3 databases – EMBASE, MEDICINE, and PubMed – were searched. The statistical data of articles which met the requirements were collated and extracted. Results: Twenty-five papers and 141 355 participants were finally enrolled. The results showed that the H. pylori infection rate of CD patients was 0.57 times greater compared to controls (OR = 0.57, 95% CI [0.44, 0.75]), while statistical differences were also seen in the subgroups of children (OR = 0.53, 95% CI [0.33, 0.85]) and adults (OR = 0.63, 95% CI [0.49, 0.81]). Furthermore, patients having CD with H. pylori were more likely to have symptoms of abdominal pain, diarrhea, and distension (OR = 2.5, 95% CI [1.35, 4.62]) (OR = 1.56, 95% CI [1.09, 2.24]) (OR = 2.75, 95% CI [1.74, 4.35]). However, H. pylori has no effect on CD classification. Conclusion: The study confirmed that there is a correlation between H. pylori and CD, but the causality cannot be clarified. A demonstration of a causal role of H. pylori in CD in future prospective studies could have important therapeutic implications. Cite this article as: Yue M, Chen Q, Zhou X, Li L, Lu C. Is Helicobacter pylori infection associated with Celiac disease? A metaanalysis. Turk J Gastroenterol. 2022;33(3):205-212.